La várico ligadura escalonada subdérmica: su uso en tratamiento de las várices del miembro inferior - Matteucci, Pablo; Sarroca, Carlos; Armand Ugon, Alfredo; Piedra-Buena, Luis; Pomi, Jorge; Tchekmedyan, Vartan (Cirugía del Uruguay, 1979)
Subdermic Staged Varicoligature is a minar procedure in surgery of lower limb varices. Its main indication is in the treatment of residual venous packages, after phleboextraction. The result is highly satisfactory from the esthetic viewpoint. The authors describe this technique in detair and consign the results obtained.